2012
DOI: 10.1016/j.cgh.2012.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Increased Bile Acid Biosynthesis Is Associated With Irritable Bowel Syndrome With Diarrhea

Abstract: BACKGROUND & AIMS Variations in genes that regulate bile acid (BA) synthesis are associated with colonic transit in patients with irritable bowel syndrome (IBS). We investigated features of BA synthesis and excretion and genetic features of patients with different types of IBS. METHODS In 26 healthy volunteers, 26 patients with IBS and constipation (IBS-C), and 26 with IBS and diarrhea (IBS-D), we measured serum levels of 7α-hydroxy-4-cholesten-3-one (C4; a surrogate for BA synthesis) and fibroblast growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
174
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(196 citation statements)
references
References 30 publications
10
174
0
6
Order By: Relevance
“…We therefore believe that, having used state of the art definitions and testing modalities, our findings are contemporary and provide compelling evidence that can be generalized to other centers seeing a similar population of patients. In fact, a recent study from the United States identified that 38% of patients with D-IBS were noted to have higher serum C4, and faecal bile acids, compared with healthy volunteers, or patients with constipation-predominant IBS 27 suggesting that, if 75 SeHCAT testing were available in the USA, the yield in patients with D-IBS is likely to be similar to ours.…”
Section: Discussionmentioning
confidence: 78%
“…We therefore believe that, having used state of the art definitions and testing modalities, our findings are contemporary and provide compelling evidence that can be generalized to other centers seeing a similar population of patients. In fact, a recent study from the United States identified that 38% of patients with D-IBS were noted to have higher serum C4, and faecal bile acids, compared with healthy volunteers, or patients with constipation-predominant IBS 27 suggesting that, if 75 SeHCAT testing were available in the USA, the yield in patients with D-IBS is likely to be similar to ours.…”
Section: Discussionmentioning
confidence: 78%
“…B3-adrenoceptor, cholinergic receptor muscarinic 3 polymorphisms, and tryptophan hydroxylase gene polymorphisms were also studied in IBS patients (27,28). Very recent studies about D-IBS patients address the genes regulating hepatic bile acid synthesis but more studies are needed to state an association (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…En los enterocitos del íleon, la unión de los AB con el FXR lleva a inducción transcripcional del factor de crecimiento del fibroblasto 19 (FGF19); la unión del FGF19 al receptor de membrana del hepatocito FGF tipo 4 (FGFR4) y su correceptor Klothob, activa vías intracelulares que disminuyen la expresión de CYP7A1 (11,20), esto es un ejemplo claro de retroalimentación negativa hígado-íleon. Se ha encontrado en distintos estudios, que explican el posible mecanismo de mala-absorción de AB, niveles bajos de FGF19 en pacientes con mala-absorción idiopática de AB e inversión de la relación FGF19 y 7 α-hidroxi-4-colesten-3-ona (C4), este último es un indicador de la síntesis de AB (21,22).…”
Section: Fisiopatologíaunclassified